Mobilidade urbana: análise da morfologia e das transformações do transporte individual na cidade de São Paulo - Vitorino, Ana Paula Corrêa (2020)
One of the major challenges facing the development of large urban centers in the megacities of the 21st century concerns the ability to adapt these cities to the huge flows of people, products and goods that need to circulate in a way fluid and efficient daily. The tangle of factors that interfere in the quality of urban displacement permeates public policies of mobility, perception of safety, prioritization of fast, light, non-motorized and non-polluting means of transport, emphasis on collective displacement in detriment of the individual, prioritization of routes of people and goods on multimodal platforms that are planned previously in order to promote urban intelligence, economy and, indispensably, speed. The large number of motor vehicles in the world's major metropolises and, specifically, in Brazil and São Paulo, impacts the quality and efficiency of urban mobility. Many solutions have been presented to supplant this challenge, such as mobility and travel sharing applications on demand. The aim of this study was to verify and discuss whether, and to what extent, the advent of technological advances and the emergence of individual displacement applications on demand impacted the forms of urban mobility in the city of São Paulo. Indirect qualitative research characterized as literature review and document analysis. From the Origin Destination Research 2017, the decennial publication of the Metropolitan of São Paulo, the transformations in the morphology of transport in general and, more precisely, in the individual motorized transport were analyzed. The results showed an increase (12.4%), between 2007 and 2017, in the use of motorized individual transport in virtually all sub-regions, except the São Paulo Center. There was a drop in the rate of use of individual motorized trips by the car (2.2%), increased use of motorcycles (31%) and displacements with taxis on demand of (425%). Structural changes in social conditions such as income, financial and professional stability and precariousness of work, school enrollment location in addition to the increase in the fixed cost of maintaining the vehicle itself contributed to the explosion of the use of taxis on demand, but which still do not represent even 2% of urban mobility in São Paulo. However, the most interesting point to be presented is that the forms of general motorized locomotion (66% - 67%) (55% - 54%) and individual (45% - 46%), general non-motorized (34% - 33%) on foot (98% - 97%) and bicycle (2% - 3%) denounce that there was no significant change in the morphology of urban mobility in the city of São Paulo between 2007 and 2017